An Effective Whistleblowing System Model for Regional Inspectorates: A Qualitative Study in Fraud Prevention - Muhyidin, Asep; Nurfauziah, Farah Latifah; Suharti, Sri (Journal of Accounting Auditing and Business, 2025)
Abstract: This study examines the effectiveness of the Whistleblowing System (WBS) in fraud prevention at the Government Inspectorate of Garut Regency, Indonesia. Using a qualitative approach and thematic analysis with NVivo, the research identifies key factors influencing WBS success, including structural, operational, and human resource aspects. Findings indicate that WBS significantly enhances transparency and accountability through accessible reporting mechanisms, whistleblower protection, and investigative follow-up. Critical determinants of effectiveness include: (1) technological support for whistleblower anonymity, (2) personnel competence in handling reports, and (3) compliance with Regulation of the Garut Regent No. 50 of 2020 on WBS implementation guidelines. Thematic nodes reveal dominant challenges: lack of socialization (35%), weak coordination (25%), ambiguous regulations (20%), and limited human resources (20%). The proposed WBS implementation model emphasizes systematic stages—from reporting to sanctions—while strengthening early detection and accountability. The study underscores the necessity of integrating policy, technology, and organizational culture to optimize WBS. Practical contributions include actionable insights for local governments to improve violation reporting systems and advance academic discourse on public-sector fraud prevention.